Pattern visual evoked responses in hereditary spastic paraplegia. Issue 2 (February 1981) - Livingstone, I R; Mastaglia, F L; Edis, R; Howe, J W
Abstract : Pattern visual evoked responses were studied in 13 patients from nine families with dominant herditary spastic paraplegia and in seven sporadic cases. The responses were normal in all the dominantly inherited cases but abnormal in three of the seven sporadic cases.